The implementation and evaluation of the ViSC program in Cyprus: challenges of cross-national dissemination and evaluation results. Issue 6 (1st November 2016) - Solomontos-Kountouri, Olga; Gradinger, Petra; Yanagida, Takuya; Strohmeier, Dagmar
Abstract: The ViSC program is a socio-ecological anti-bullying program that has been developed, implemented and rigorously evaluated in Austria. The main goals of the present study were (1) to implement the ViSC program with high fidelity in Cyprus and (2) to investigate the program effectiveness within a quasi-experimental longitudinal study. To tackle bullying on different levels in the educational system, a cascaded train-the-trainer model has been realized. Nine permanent staff members of the Cypriot Ministry of Education were trained as multipliers by researchers. These multipliers trained teachers in three Cypriot schools and teachers trained their students. To investigate the effectiveness of the program, data from students of three intervention and three control schools was collected via self-assessments at pre-test (October–November 2012), post-test (April–May 2013) and follow-up (March–April 2014). In total, 1752 grade 7 and 8 students (602 intervention, 1150 control group) with a mean age of 12.6 (SD = .60) at pre-test, nested in 82 classes and 6 schools participated. To investigate the program effectiveness regarding the reduction of victimization and aggressive behavior, multilevel growth models were applied (time points at level 1, individuals at level 2, and classes at level 3). The analyses revealed that the program effects differed depending on the grade level of the students. Overall, the program was more effective for grade 7 compared with grade 8 students. In grade 8, bullying and victimization increased more in the intervention group compared with the control group at time 2, but also steeper decreased at time 3 indicating a sensitizing effect of the program.